Reformasi Birokrasi Dalam Pelayanan Publik di Direktorat Jenderal Imigrasi (Studi pada Kantor Imigrasi Kelas I Khusus Surabaya) - Harvijan Dwi Ashri Yahya (Jurnal Administrasi Publik, 2014)
Abstract: Bureaucratic Reform of Public Service in the Directorate General of Immigration (Studies in Special Immigration Office Class I Surabaya). In 2010 appeared a concept and a comprehensive policy and Bureaucratic Reform established by Presidential Decree 81 of 2010 on the Grand Design Bureaucratic Reform from 2010 to 2025, and the Regulation of the Minister of Administrative Reform and Bureaucratic Reform No. 20 Year 2010 on Bureaucratic Reform Road Map 2010-2014. Special Immigration Office Class I Surabaya as a Technical Implementation Unit of the Directorate General of Immigration in the field of immigration is expected to perform his duties as a public servant. The results of this study indicate that the acceleration process is to be obtained from the passport service in the Special Immigration Office Class I Surabaya is creating a service to the community as well as possible with the principles of excellent service. From the data obtained the new passport applicants want the speed of time, cost certainty, and ease of the procedure. The community desires can be answered by the Directorate General of immigration and Immigration Office Class I Special Surabaya with the advent of a Flow Service One Stop Service, which is more efficient services to the community in the process of making application for a new passport. Keywords: bureaucratic reform, improvement public services, one stop service, Special Immigration Office Class I Surabaya Abstrak: Reformasi Birokrasi dalam Pelayanan Publik Di Direktorat Jenderal Imigrasi (Studi pada Kantor Imigrasi Kelas I Khusus Surabaya). Pada tahun 2010 muncul sebuah konsep dan kebijakan Reformasi Birokrasi yang komprehensif dan ditetapkan dengan Peraturan Presiden No.81 Tahun 2010 tentang Grand Design Reformasi Birokrasi 2010-2025, dan Permenpan-rb No. 20 Tahun 2010 tentang Road Map Reformasi Birokrasi 2010-2014. Kantor Imigrasi Kelas I Khusus Surabaya sebagai Unit Pelaksana Teknis Direktorat Jenderal Imigrasi di bidang keimigrasian diharapkan mampu melaksanakan tugas-tugasnya sebagai pelayan masyarakat. Hasil Penelitian ini menunjukkan bahwa yang ingin diperoleh dari proses percepatan pelayanan paspor di Kantor Imigrasi Kelas I Khusus Surabaya adalah menciptakan pelayanan kepada masyarakat dengan sebaik-baiknya dengan prinsip pelayanan prima. Dari data yang diperoleh para pemohon pembuatan paspor baru, menginginkan adanya kecepatan waktu, kepastian biaya, dan kemudahan prosedur. Keinginan masyarakat tersebut mampu dijawab oleh Direktorat Jenderal Imgrasi dan Kantor Imigrasi Kelas I Khusus Surabaya dengan munculnya sebuah Alur Pelayanan One Stop Service, yaitu pelayanan yang lebih efisien kepada masyarakat dalam proses permohonan pembuatan paspor baru. Kata Kunci : reformasi birokrasi, peningkatan pelayanan publik, one stop service, Kantor Imigrasi Kelas I Khusus SurabayaÂ